Pengaruh Faktor Pola Asuh Orang Tua, Kompetensi Pedagogik Guru dan Motivasi Berprestasi terhadap Prestasi Belajar Siswa di SMA Negeri Satu Atap Lembongan - Candra Manik Maheyeti; I Putu Wisna Ariawan; Ni Luh Gede Erni Sulindawati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The research in this thesis is motivated by the many teacher competencies that have not been achieved in accordance with the National Education System Law No. 20 of 2003 Article 39 Paragraph 2. And also the parenting style of parents who tend not to support children's education because they have to help parents because of work and economic demands. The type of research used by this research is quantitative research with an "ex-post facto" approach. Data collection is carried out by questionnaire instrument. Data analysis and hypothesis testing in this study used multiple regression. The results showed (1) There is a significant influence between parenting style on student achievement at SMA Negeri Satu Atap Lembongan as shown from tcalculate > ttable (3,840 > 1.972), the significance value of t for the parenting variable is 0.000 and the value is smaller than the probability of 0.05 (0.000 < 0.05) (2) There is a significant influence between teacher pedagogic competence on student achievement at SMA Negeri Satu Atap Lembongan Shown from tcount > ttable (2.920 > 1.972). The significance value of t for the teacher's pedagogic competency variable is 0.004 and the value is smaller than the probability of 0.05 (0.004 < 0.05). (3) There is a significant influence between achievement motivation on student achievement at SMA Negeri Satu Atap Lembongan as shown from the ttable > (2,314 > 1,972). The significance value of t for the motivational variable is 0.021 and the value is smaller than the probability of 0.05 (0.021 < 0.05). (4) There is a significant influence between parenting, teacher pedagogic competence and achievement motivation on student achievement at SMA Negeri Satu Atap Lembongan as shown from Fhitung > Ftabel (11,975> 2.65). The significance value of the concurrent test (F test) is 0.000 and the value is smaller than the probability of 0.05 (0.000 < 0.05).